A variational inequality theory in reflexive smooth Banach spaces and applications to p-Laplacian elliptic inequalities. (January 2015) - Lan, Kunquan
Abstract: We develop a theory of variational inequality for demicontinuous S -contractive maps in reflexive smooth Banach spaces. Variational inequality theorems are proved and applied to study existence of nonzero positive weak solutions for p -Laplacian elliptic inequalities and a population model of one species arising in mathematical biology.